2011
DOI: 10.1002/biot.201100122
|View full text |Cite
|
Sign up to set email alerts
|

Poly(3‐hydroxybutyrate) production by Bacillus cereus SPV using sugarcane molasses as the main carbon source

Abstract: The main hindrance in the use of polyhydroxyalkanoates (PHAs) as a replacement for existing petroleum-based plastics is their high production cost. The carbon source accounts for 50% of the cost for PHA production. Thus, increasing the yield and productivity of PHAs on cheap substrates is an important challenge for biotechnologists to support the commercialization and further applications of these polymers. In this study, we have investigated the use of an agricultural raw material, sugarcane molasses, as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 24 publications
2
24
3
Order By: Relevance
“…However, quite interestingly, there have been only few reports on the utilization of pure or refined substrates (sugars) for P(3HB) production, [27][28][29][30] while different types of inexpensive carbon sources such as agro-industrial wastes including cane molasses, sugar beet juice, rice straw hydrolysate, grass biomass hydrolysate, plant oils e.g., coconut oil, have been largely investigated. [31][32][33][34][35][36][37][38] Alcaligenes and Bacillus sp. remain the microorganisms of choice for P(3HB) production (Table 1).…”
Section: Batch Fermentationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, quite interestingly, there have been only few reports on the utilization of pure or refined substrates (sugars) for P(3HB) production, [27][28][29][30] while different types of inexpensive carbon sources such as agro-industrial wastes including cane molasses, sugar beet juice, rice straw hydrolysate, grass biomass hydrolysate, plant oils e.g., coconut oil, have been largely investigated. [31][32][33][34][35][36][37][38] Alcaligenes and Bacillus sp. remain the microorganisms of choice for P(3HB) production (Table 1).…”
Section: Batch Fermentationmentioning
confidence: 99%
“…62 Another fed-batch strategy involving substrate feeding at a constant feed rate for P(3HB) production has been described. 31,64 A novel exponential feeding strategy based on alkali-addition monitoring was developed to maintain waste glycerol (substrate) at a constant level inside the bioreactor. 65 It resulted in a significantly high P(3HB) concentration of 65.6 g L -1 , yield of 62.7 % dcw, and productivity of 1.3 g L -1 h -1…”
Section: Fed-batch Fermentationmentioning
confidence: 99%
“…Being the unwanted waste from food industry, WCO also demonstrates its value as substrate for PHA production (1.180 USD$/kg PHA). Agreeing with the literature (Akaraonye et al 2012), further analysis has shown that carbon source has dominated the share of raw material cost which contribute at least 66.3 % of the total cost. Internal rate of return (IRR) and total annual cost (TAC) have always been used by the literature (Gurieff and Lant 2007;Van Wegen et al 1998;Choi et al 2010) to evaluate economic performance of PHAs biosynthesis process.…”
Section: Economic Assessment Of Pha Biosynthesismentioning
confidence: 72%
“…For the determination of PHB content, the GC method of Akaraonye et al with slight modification was employed (Akaraonye et al 2012). 2 mL of chloroform and 2 mL of acidified methanol which contained 1 % v/v of sulphuric acid were added to approximately 20-mg dried samples.…”
Section: Biomass Determination and Pha Content Analysismentioning
confidence: 99%
“…[326] Sinorhizobium meliloti 41 and Hydrogenophaga pseudoflava DSM 1034 can biosynthesize P(3HB), P(3HB-co-3HV) copolyesters, and P(3HB-co-3HV-co-4HB) terpolyesters from lactose. [329][330][331] Furthermore, PHAs can also be produced directly from molasses (e.g.,s ugarcane, sugar beet,a nd soy molasses), ahigh sucrose content byproduct from the sugar industry,o ro ther sucrose-rich products (e.g.,m aple sap, sugar beet juice, pineapple juice, or oil palm frondj uice) by using C. necator, [332] A. vinelandii, [331] Enterobacter species, [333] Pseudomonas corrugate, [334] A. latus, [335] recombinant E. coli, [336,337] B. subtilis, [337] B. megaterium, [338] Bacillus cereus, [339] or mixed cultures. [327] Sucrose, ad isaccharide composed of ag lucosea nd af ructose unit, is one of the most abundant and relativelyi nexpensive carbon sources extracted from sugar-bearing raw materials, such as sugar beet and sugarcane.…”
Section: Carbohydratesmentioning
confidence: 99%